1999
DOI: 10.1016/s0029-7844(98)00529-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in obstetricians? offices: a survey study*1

Abstract: Obstetricians' knowledge of inheritance and test selection pertaining to single-gene disorders was more limited than that for aneuploidy and neural tube defects. Comparable deficits were noted in patient-education efforts for single-gene disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…9 On the basis of similar studies conducted by ACOG, where preliminary power analyses indicated that the minimum number of responses needed to ensure significant effect sizes was approximately 100, our sample size was deemed sufficient. 10 All non-respondents received a second mailing of the questionnaire four weeks after the first mailing. Questionnaires returned by 10 June 2003 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…9 On the basis of similar studies conducted by ACOG, where preliminary power analyses indicated that the minimum number of responses needed to ensure significant effect sizes was approximately 100, our sample size was deemed sufficient. 10 All non-respondents received a second mailing of the questionnaire four weeks after the first mailing. Questionnaires returned by 10 June 2003 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was developed by a panel of clinicians and researchers with expertise in carrier screening programs and was informed by previous international studies (Morgan et al, 2004(Morgan et al, , 2005Wilkins-Haug et al, 1999). The survey was reviewed by the RANZCOG Continuing Professional Development committee, and the content was modified in response to their feedback.…”
Section: Measurement Toolmentioning
confidence: 99%
“…An increased awareness among people about genetic risk factors may be present during pregnancy, as has been stated by Lubin et al [39] and Wilkins-Haug et al [25]. In addition, Gibb et al [27] found in a group of insulin-dependent diabetic women that they were all aware of the importance of good blood glucose control during pregnancy.…”
Section: Resultsmentioning
confidence: 92%
“…Most of the selected studies were essentially descriptive in nature (see table 1). In the research papers, data were collected by self-report, including self-created data collection forms in nine studies [17,18,19,20,21,22,23,24,25] and semi-structured interviews in five studies [26,27,28,29,30] and by studying medical records in six studies [31,32,33,34,35,36]. Furthermore, we included seven literature reviews [37,38,39,40,41,42,43], six case reports [44,45,46,47,48,49] and one study, in which a mathematical model was used [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation